IFPortal – a web portal for the characterization and comparison of government interoperability frameworks - Campos, Luís Filipe Gomes (2014)
The search for better and more adequate levels of government information systems interoperability led many governments all over the world to develop, adopt and publish what is known as e-government interoperability frameworks – documents that specify a set of common elements such as vocabularies, concepts, principles, policies, guidelines, recommendations, standards, and practices for agencies that wish to work together, towards the joint delivery of public services. The central purpose of this paper is to present a detailed description of a portal — IFPortal — that could provide a simple and appropriate way to aggregate, analyze, compare, and display information about e-government interoperability frameworks. Such a portal will enable the registration, search, visualization, analysis, and comparison of interoperability frameworks’ content, structure and scope, thus allowing for the identification of similarities and differences among them. An IFPortal prototype, already developed, is also presented and may be accessed in order to exemplify the IFPortal concept.